ANALISA KESEHATAN KEUANGAN PT. BANK BUKOPIN TBK - Rina Nopianti (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2017)
Bank Bukopin (Persero) Tbk is one of the Indonesian government-owned banks. Bank Bukopin continuously conducts evaluations and improvements, especially in the areas of service, product development, marketing functions and development of office network, in order to realize the vision as a trusted bank in financial services. This is evident from the analysis of financial performance in the period 2014-2016 which shows an increasing trend every year. The purpose of this study are: "To analyze / know the financial performance at PT. Bank Bukopin Tbk year 2014-2016 using CAMEL method This research uses descriptive analysis method, that is explaining the rating of bank soundness by using CAMEL method. Model of data analysis method used is descriptive analysis model. Based on CAMEL method analysis, PT. Bank Bukopin Tbk is a well-respected banking company. This is indicated by the value of CAMEL from 2014 to 2016 in a row is 85.31; 83.89 and 83.09. Based on the calculation results, it can be seen that PT. Bank Bukopin Tbk can still continue its business, although during the period 2014 to 2016 the value of CAMEL PT. Bank Bukopin Tbk experienced a downward trend. It also shows that during the same period, PT. Bank Bukopin Tbk has a good performance in the management of all the resources it has when viewed based on CAMEL Ratio calculation results